Youth use of e-cigarettes: Does dependence vary by device type?. (August 2021) - Tackett, Alayna P.; Hébert, Emily T.; Smith, Caitlin E.; Wallace, Samantha W.; Barrington-Trimis, Jessica L.; Norris, Jordan E.; Lechner, William V.; Stevens, Elise M.; Wagener, Theodore L.
Highlights: Features of nicotine dependence among youth differed by primary e-cigarette device used. Pod mod users reported increased nicotine dependence compared to other device types. Youth endorsed an average of 4.5 out of 10 HONC symptoms. The number of positive HONC responses reflects the degree of dependence. Abstract: Introduction: Youth nicotine dependence may vary by e-cigarette device used. Methods: E‐cigarette device type ("JUUL, " "similar pod/JUUL like device (i.e., pod mod), " or "other type of e-cigarette" (i.e., tank, mod)), nicotine dependence (Hooked on Nicotine Checklist; HONC), frequency of e-cigarette use (i.e., weekly, daily, monthly), and covariates were examined via a convenience sample of youth who use e-cigarettes in the United States via an online Qualtrics panel survey from April 2019 to May 2019. Results: Youth aged 13–17 (Mean age = 15.9 years, SD = 1.0 year; n  = 185) were mostly 72.4% female. Primary device used by category was endorsed as follows: JUUL n  = 87, pod mod n  = 42, and other type of e-cigarette n  = 56. Participants endorsed an average of 4.5 / 10 HONC symptoms ( SD  = 3.6). Compared to other e-cigarettes, youth who used JUUL and pod mod devices endorsed more dependence symptoms, even when adjusting for current smoking status (JUUL IRR = 1.96, 95% CI 1.30–2.97; pod mod device IRR = 1.76, 95% CI 1.08–2.87). In total, HONC symptoms significantly differed by device for 8/10 symptoms, with JUUL and pod mod users reporting higher frequency of items compared to other e-cigarette devices. Conclusions: Features of nicotine dependence experienced by youth (i.e., feeling a stronger urge to vape) differed by primary device used, with those using JUUL and pod-mods reporting a greater level of dependence. Regulation of features of e-cigarette devices that may increase nicotine delivery and subsequent development of dependence among youth warrant urgent consideration.